1994
DOI: 10.1177/107769909407100308
|View full text |Cite
|
Sign up to set email alerts
|

Local Breaking News: Sources, Technology, and News Routines

Abstract: The contribution of electronic information technologies to breaking general assignment and routine beat news stories in large metropolitan newspapers is examined through a content analysis and in-depth interviews with reporters. Reporters working on breaking news stories make hea y use of their own paper's electronic bacqles and of fax technology, but do not use other information technologies available to them. Reporters use multiple sources for their stories and claim that electronic information technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…News sources shaped the news agenda in national and regional newspapers (Salwen, 1995). Studies conducted in the US reported an increasing use of multiple news sources, as opposed to a single source, in both small and large daily newspapers, although the sources used represented the same power structures as before (Hansen, Ward, Conners, & Neuzil, 1994). Official sources and experts' quotations were found to dominate news content (Fico, 1985;Smith, 1993), as official and experts were more likely to be treated as 'fact providers' (BarkerPlummer, 1989).…”
Section: News Source Researchmentioning
confidence: 98%
“…News sources shaped the news agenda in national and regional newspapers (Salwen, 1995). Studies conducted in the US reported an increasing use of multiple news sources, as opposed to a single source, in both small and large daily newspapers, although the sources used represented the same power structures as before (Hansen, Ward, Conners, & Neuzil, 1994). Official sources and experts' quotations were found to dominate news content (Fico, 1985;Smith, 1993), as official and experts were more likely to be treated as 'fact providers' (BarkerPlummer, 1989).…”
Section: News Source Researchmentioning
confidence: 98%
“…She would talk and I could hear -I was there till about 4amand I would hear her almost on autopilot saying the same thing over and over. (Binning, interview) When breaking news occurs, journalists on the spot are the ones who gather the information but supplementary information is needed to produce a comprehensive report (Hansen et al 1994). Editors interviewed for this study highlight the fact that journalists on the spot 'work in a bubble' (Clark, interview) knowing only part of the story they collected, not the whole story.…”
Section: Friday Afternoon Breaking Newsmentioning
confidence: 99%
“…Comprehensive news coverage is only possible through reliable and informative news sources. A story without sources to confirm or deny information, will not air (Gans, 1980;Hansen & Ward, 1994). With the PPACA, the only available source was the White House.…”
Section: Journalism Routines and Practicesmentioning
confidence: 99%